The Sooner (and the Smarter), the Better : COVID-19 Containment Measures and Fiscal Responses - Hosny, Amr (IMF Working Papers; Working Paper ;, 2021)
This paper finds empirical evidence that faster and smarter containment measures were associated with lower fiscal responses to the COVID-19 shock. We also find that initial conditions, such as fiscal space, income, health preparedness and budget transparency were important in shaping the amount and design of the COVID-19 fiscal response.